Environmental surfaces and the compression of perceived visual space - Bian, Zheng (2011)
The present study examined whether the compression of perceived visual space varies according to the type of environmental surface being viewed. To examine this issue, observers made exocentric distance judgments when viewing simulated 3D scenes. In 4 experiments, observers viewed ground and ceiling surfaces and performed either an L-shaped matching task (Experiments 1, 3, and 4) or a bisection task (Experiment 2). Overall, we found considerable compression of perceived exocentric distance on both ground and ceiling surfaces. However, the perceived exocentric distance was less compressed on a ground surface than on a ceiling surface. In addition, this ground surface advantage did not vary systematically as a function of the distance in the scene. These results suggest that the perceived visual space when viewing a ground surface is less compressed than the perceived visual space when viewing a ceiling surface and that the perceived layout of a surface varies as a function of the type of the surface.